Associate problems in implementation of Industrialised Building System (IBS) in construction industry in Selangor / Izmaazura Ismail - Ismail, Izmaazura (2006)
For years, construction is known as significant economic sectors, which have provided important catalyst to Malaysia’s economic development. Propelling the engine of growth, it helps Malaysia realize its vision of becoming an industrialized nation by 2020. Directly and indirectly, Malaysia has immensely benefited from its construction sector in the form of economic and social developments. If the building processes in our construction sector are made more efficient, potential benefits to the country and contractors may even be greater. The mechanism that is bound to enhance the value to our construction sector is ‘industrialised Building Systems (IBS)’.1 Industrialised method of construction has become the catchwords in the building and housing industries in this part of the region.